ANALYSIS OF INDIGENOUS PRACTICES OF SMALL-SCALE PLANTAIN FARMERS FOR APPROPRIATE ALLEY FARMING TECHNOLOGY IN OYO STATE, NIGERIA (1992)
The limitations of conventional technology development gave birth to Farming Systems Research perspective which look at farming practices from a holistic view. This however has innate flaws in its implementation. Recent emphasis therefore is strengthening the need to appreciate a hitherto neglected indigenous knowledge systems. This indigenous knowledge for instance, has been influencing the indigenous practices associated with small-scale plantain production. Before now Plantain has not received favourable attention despite its economic potentials in the Nigerian economy. This is the main reason for this investigation which described the indigenous practices in its production. It is with an intent to illustrate how Alley Farming Technology should be designed to blend with the indigenous practices of the small-scale plantain farmers. The inquiry was conducted in Irewole and Oranmiyan Local Government Areas (LGAs) of Oyo State (however, since the creation of new states in 1992, these LGAs have become part of Osun State). The objectives of the study were to: describe the socio-economic features of plantain farmers, ascertain their indigenous practices, identify constraints to production, examine their agricultural information sources and determine the impact of certain variables on indigenous practices. A mini-study (or field observation) was conducted on ten small-scale (volunteer- farmers less than 3 ha) plantain plots. The monitoring of these plots for about six months was to field-test certain concepts which were empirically investigated in the follow-up survey. The survey was an interview schedule administered to two hundred and seventy (270) small-scale plantain farmers selected through a multi-stage sampling technique in the two LGAs. Frequency analysis of information obtained from the ten plots indicated that the most common crops intercropped with plantain (26.2%) were cassava, cocoyam, maize and vegetables. Information from the questionnaire revealed that 91% of the respondents had no formal education. Though staking was a practice, recommended spacing and mulching of plantain was not favoured by 98% of the interviewees. Cutlass was frequently used by 99.3% in plantain operations. Male household heads determined planting plantain (99.3%), plots to be used (98.9%) while female household heads/wives of male household heads decided on plantain processing (78.5%), sales (89.6%) and cost of production (69.6%). Constraints to plantain production include declining soil fertility (98.5%), insufficient propagules (95.2%) and inadequate extension service (95.9%). Multipurpose trees (MPTs) known to plantain farmers were Cassia (98.1%) and Gliricidia (97.0%). At a priori P<.05, pearson correlation analysis indicated a significant and positive association between indigenous knowledge and intercropping of plantain (r = 0.25). Use of Radio as a source negatively correlated with staking (r=-0.51) and mulching of plantain (r = -0.23). Stepwise multivariate ^egression showed that 48% of the variation in indigenous intercropping of plantain was explained by six regressors; household size, social participation, alley farming awareness, extension drama method, farm service centres and poor community market prices for plantain. These findings have implications for the adoption of Alley Farming technology in the study area. There is a serious need to involve small-scale plantain farmers in alley species (MPTs) selection, establishment and management. A comprehensive extension educational programme is necessary to make plantain farmers more aware of the alley farming technology.